Kepala Keluarga dalam Islam (Telaah QS. Al-Nisa: 34) - Ahmad Afifuddin Al Amin (JURNAL INDO-ISLAMIKA, 2011)
This article discusses the head of family in Islam by examining surah al-Nisa: 34. This paper is a qualitative study using the Charles Sanders Peirce semiotic approach. This research is study literature. The sources in this study are kitab, books and journal articles that are relevant to the theme. Interpretation of QS. An-Nisa (4): 34 by taking some references to the views of the previous ulama, it can be concluded that men are the head of the "leader" family in a family setting.